2021
DOI: 10.1038/s41598-021-89734-y
|View full text |Cite
|
Sign up to set email alerts
|

LSD1-mediated demethylation of OCT4 safeguards pluripotent stem cells by maintaining the transcription of PORE-motif-containing genes

Abstract: Reversible lysine methylation is essential for regulating histones and emerges to critically regulate non-histone proteins as well. Here we show that the master transcription factor OCT4 in pluripotent stem cells (PSCs) was methylated at multiple lysine residues. LSD1 that is highly expressed in PSCs can directly interact with and demethylate OCT4 at lysine 222 (K222) in the flexible linker region. Reduced LSD1 activity led to the methylation of OCT4-K222 that diminished the differentiation potential of PSCs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Hence, it has been shown that LSD1 promoted OCT4 protein stability in pluripotent stem cells (PSCs) by demethylating OCT4 at the residue K222. Un-methylated OCT4-K222 was prevented from proteasome-independent degradation and thereby, LSD1-mediated demethylation of OCT4 promoted the transcription of PORE-motif genes preserving PSCs pluripotency (Figure 3B) [63]. In addition, LSD1 was reported to be critical for the maintenance of human ESCs through the silencing of developmental genes regulated by H3K4me2/3 and H3K27me3 markers by positioning in enhancers co-occupied by OCT4 and NANOG [97].…”
Section: Lsd1: Self-renewal or Pluripotency?mentioning
confidence: 98%
See 1 more Smart Citation
“…Hence, it has been shown that LSD1 promoted OCT4 protein stability in pluripotent stem cells (PSCs) by demethylating OCT4 at the residue K222. Un-methylated OCT4-K222 was prevented from proteasome-independent degradation and thereby, LSD1-mediated demethylation of OCT4 promoted the transcription of PORE-motif genes preserving PSCs pluripotency (Figure 3B) [63]. In addition, LSD1 was reported to be critical for the maintenance of human ESCs through the silencing of developmental genes regulated by H3K4me2/3 and H3K27me3 markers by positioning in enhancers co-occupied by OCT4 and NANOG [97].…”
Section: Lsd1: Self-renewal or Pluripotency?mentioning
confidence: 98%
“…In general, LSD1-mediated demethylation alters both the function and the stability of the target protein. Such substrates include proteins with important implications in stem cell biology (Table 2) being DNMT1 and OCT4 amongst them which will be further discussed in this review [10,63]. It associates with Setd1a/COMPASS complex to maintain mesoderm and neuroectoderm histone marks, ensuring a proper differentiation in stem cells.…”
Section: Non-canonical Targets Of Lsd1 Beyond Demethylation Of Histon...mentioning
confidence: 99%